Perancangan Sistem Peminjaman Papan Surfing Menggunakan Rfid, Barcode Scanner Dan Delphi 7 - Riska Amelia; Rini Sovia; Ruri Hartika Zain (Journal of Computer Scine and Information Technology, 2024)
Water surfing has become a tourism industry worth billions, where millions of surfers travel around the world to several water surfing destinations in search of the 'perfect wave'. It is now estimated that there are more than 10 million water surfers in the world and this continues to increase at 12-16% per year. These surfers also visit places in the world that they feel are in harmony with what they are looking for. In one place they visited there were surfboard rental kiosks.Surfboard rental service sellers will serve visitors to rent their surfboards. Because there are too many surfboard enthusiasts, it is too difficult for surfboard rental service sellers to serve visitors. From these problems, a system is needed that can simplify the process and data collection of surfboard borrowing.